Wheel of knowing [videorecordings] : A story of hope - Heartshaper Video (Philippines : Lighthouse Educational Corp., 2009)
Melanie has a life all figured out... into her home.
General audience.
Keywords: Christian life $1 (BDrama.s -- Hope (Psychological aspects) $1 (BReligious aspects $1 (BChristianity $1 (BDrama.s